Update of Modified Version of the Foot Function Index Tool Spanish Version (FFI-Sp), in Patients with Rheumatoid Arthritis: Cross Sectional Study. - Gámez-Guijarro, Maria; Reinoso-Cobo, Andrés; Gordillo-Fernández, Luis; Ortiz-Romero, Mercedes; Ortega-Ávila, Ana Belén; Chicharro-Luna, Esther; Gijón-Noguerón, Gabriel; Lópezosa-Reca, Eva (MDPI, 2024)
Background and Objectives: The Foot Function Index (FFI) is a widely recognized patient-reported outcome measure (PROM) for assessing foot functionality and its impact on quality of life in individuals with rheumatoid arthritis (RA). This study aimed to observe the behavior of the tool in the Spanish population with RA, optimize the tool, and check its functionality. Materials and Methods: A total of 549 RA patients, with a predominant female participation (75.6%). This study involved a comprehensive statistical analysis, leading to a refined version of the FFI for a Spanish-speaking population. Results: The original 23-item FFI was revised, resulting in a 15-item version by excluding items that caused confusion or were considered redundant. This modified version maintained the original’s subscales of pain, disability, and activity limitation, but with an adjusted item distribution. The construct validity was confirmed through exploratory factor analysis, demonstrating excellent fit indices (Kaiser–Meyer–Olkin test = 0.926, Bartlett’s test of sphericity = 4123.48, p < 0.001). The revised FFI demonstrated good internal consistency (Cronbach’s alpha = 0.96) and test–retest reliability (ICC = 0.89). Conclusions: This study highlights the applicability of the FFI in Spanish-speaking RA populations, offering a valid and reliable tool for clinicians and researchers. The modifications enhance the FFI’s relevance for RA patients, facilitating better assessment and management of foot-related functional impairments.
Keywords: Artritis reumatoide; Pies; Pacientes; Foot; Rheumatoid Artritis; Patient-reported outcome measures; Function